Respuesta :

Answer:

81.5

Step-by-step explanation:

<G and <H are congruent

<F and <I are congruent

so the last two angles in both triangles must also be congruent

this means that <K and <J are congruent

so we can create this equation: <K = <J

substitute the angles with what we know: 4[tex]y^{2}[/tex] = 6[tex]y^{2}[/tex] - 40

add 40 to both sides and subtract 4[tex]y^{2}[/tex] from both sides: 40 = 2[tex]y^{2}[/tex]

you get: 20 = [tex]y^{2}[/tex]

root square on both sides: [tex]\sqrt{20}[/tex] = [tex]\sqrt{y^{2} }[/tex]

you get: y ≈ 4.5

substitute this into one of the equations for a missing variable:

6[tex]y^{2}[/tex] -----> 6 (4.5 x 4.5) - 40

6 ( 20.25) - 40

121.5 - 40

81.5

ACCESS MORE